PERANCANGAN ALAT PENGEREMAN OTOMATIS PADA MOBIL LISTRIK DENGAN SENSOR ULTRASONIK BERBASIS MIKROKONTROLER AT89S52 - Nurhadi, Nurhadi; Maimunnah, Maimunnah (JREC (Journal of Electrical and Electronics), 2015)
Technology exists to provide convenience to the problems faced by the community . Has made Detector SystemSensor Ultrasonic Distance With Electric Car Based On AT89S52 Microcontroller . This system is a system ofmonitoring and automatic control of the vehicle distance . This system consists of hardware and software . Thehardware consists of a microcontroller AT89S52 , IC LM358 , Ultrasonic Sensors , the system software has beendesigned using assembly language programs . This application works when turned on , the hardware inisilisasi donethen giving out signs that are detected by the ultrasonic sensor LED and Buzzer . Setting if the detec ted object isgetting closer then decide relay voltage on the electric car so that the car can only be stopped slowly.